2014
DOI: 10.1371/journal.pone.0090468
|View full text |Cite
|
Sign up to set email alerts
|

“cu-coo”: Can You Recognize My Stepparents? – A Study of Host-Specific Male Call Divergence in the Common Cuckoo

Abstract: The presence of multiple host-specific races in the common cuckoo Cuculus canorus has long been recognized as an evolutionary enigma but how this genetic divergence could be maintained is still equivocal. Some recent studies supported biparental genetic contribution in maintaining the host-races, implying the necessity that they should recognize and mate assortatively with those who belong to the same host-race. One potential mechanism to accomplish this is that males may produce distinctive calls according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…Studies of male cuckoos in Korea using Principal Component Analyses (PCA) and ANOVA tests revealed that individual males produce different calls in terms of spectral and temporal features and that betweenmale variation was also greater than within-individual variation (see Jung et al 2014). DFA has also been used successfully to achieve almost 100% correct rate of classifying calls to individual males, indicating very high variability in the call characteristics between different males (Zsebők et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of male cuckoos in Korea using Principal Component Analyses (PCA) and ANOVA tests revealed that individual males produce different calls in terms of spectral and temporal features and that betweenmale variation was also greater than within-individual variation (see Jung et al 2014). DFA has also been used successfully to achieve almost 100% correct rate of classifying calls to individual males, indicating very high variability in the call characteristics between different males (Zsebők et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…3. 1-day: calls from the same day; 2-day: calls from two consecutive days; 3-day: calls from days with two days interval; 4-day: calls from days with 3 days interval; 5-day: calls from days with 4 days interval expend a lot of time and energy dealing with territorial disputes with neighbors, so recognizing different individuals would be beneficial for males by reducing the need for territorial conflict (Jung et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For cuckoos, a well‐studied brood parasitic avian species, the temporal and frequency variables of male “cu‐coo” calls (Figure a) are well‐known (Lei, Zhao, Wang, Yin, & Payne, ). This call type is sufficient to provide individual information (Jung, Lee, & Yoo, ; Li, Xia, Lloyd, Li, & Zhang, ; Zsebök, Moskat, & Ban, ), which can be used to distinguish between neighbors and strangers (Moskát, Elek, Ban, Geltsch, & Hauber, ; Moskát et al, ): Male cuckoos show less aggressive response to familiar “ cu‐coo ” calls from neighbors than unfamiliar “ cu‐coo ” calls from strangers during playback experiments. Besides the characteristic and conspicuous two‐element “ cu‐coo ” calls, males can also utter a three‐element “ cu‐cu‐coo ” call (Figure b) which contains a repeat of the first element of the regular “ cu‐coo ” call (Lei et al, ; Payne, ).…”
Section: Introductionmentioning
confidence: 99%
“…For cuckoos, a well-studied brood parasitic avian species, the temporal and frequency variables of male "cu-coo" calls ( Figure 1a) are well-known (Lei, Zhao, Wang, Yin, & Payne, 2005). This call type is sufficient to provide individual information (Jung, Lee, & Yoo, 2014;Li, Xia, Lloyd, Li, & Zhang, 2017;Zsebök, Moskat, & Ban, 2017), which can be used to distinguish between neighbors and strangers (Moskát, Elek, Ban, Geltsch, & Hauber, 2017;Moskát et al, 2018):…”
Section: Introductionmentioning
confidence: 99%